Study on Status of Women In India Sponsored By the Department of Social Welfare, Government of India: - (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Afterindependence, with the introduction of new Panchayati Raj and communitydevelopment schemes, constitutional provisions were made for the upliftment ofwomen. The spread of education, emergence of political parties, increasingurban contacts, fast means of communication and the impact of mass-media havebrought in a rapid social change in the rural community which paved the wayupto some extent, for the political participation of the rural women. The ruralwomen herself has also started realizing gradually, the importance ofparticipation in the democratic process of the country.